Optimizing the E-commerce Curriculum System in Higher Vocational Colleges from the Perspective of Industry-Education Integration - Liang Baihan; Erny Roesminingsih; Nunuk Hariyati (MASI Mandiri Edukasi, 2026)
The rapid expansion of the digital economy has increased pressure on higher vocational institutions to ensure that e-commerce curricula remain aligned with evolving industry demands. However, limited empirical attention has been given to how students perceive the optimization of the e-commerce curriculum system within the framework of industry-education integration. This study, therefore, aimed to examine students' perceptions of e-commerce curriculum optimization in a Chinese higher vocational education setting. A quantitative cross-sectional survey with a descriptive-exploratory orientation was employed. Data were collected from 32 students at Guangdong Province Huali Technician College, China, using a 30-item questionnaire measured on a five-point Likert scale. The instrument covered five dimensions: Current Curriculum Issues, School-Enterprise Collaboration, Curriculum Optimization, Teaching and Evaluation, and Safeguard Measures. Data were analyzed using descriptive statistics and Cronbach’s alpha. The results showed an overall mean of 3.672, indicating a moderately positive orientation toward curriculum reform. Safeguard Measures obtained the highest mean (3.953), followed by Curriculum Optimization (3.859), School-Enterprise Collaboration (3.703), and Teaching and Evaluation (3.667), while Current Curriculum Issues recorded the lowest mean (3.177). The overall instrument demonstrated excellent reliability (α = 0.921), although the Current Curriculum Issues subscale showed very weak internal consistency, so interpretations related to this dimension should be treated cautiously. Overall, the findings suggest that students perceive curriculum optimization primarily as a practice-oriented, institutionally supported reform process involving stronger enterprise collaboration, structured implementation mechanisms, and workplace-linked learning. As the study is exploratory and based on a single institutional context, it offers context-specific evidence for prioritizing institutionalized and practice-based reform in vocational e-commerce curricula.